Effects of a mindfulness intervention on emotion differentiation and heart rate variability - Guendelman, Simón; Lutz, Martina; Koenig, Julian; Bayer, Mareike; Dziobek, Isabel (Frontiers in Human Neuroscience, 2025)
This study explored the impact of a mindfulness-based intervention (MBI) on mental health and emotion regulation mechanisms, particularly focusing on the top-down and bottom-up related processes, such as emotion differentiation and heart rate variability (HRV). Participants underwent an 8-week mindfulness-based stress reduction (MBSR) program or a reading-sharing intervention (READ). Emotion differentiation and HRV were measured at various intervals, alongside mental health measurements (depressive and stress symptomatology, wellbeing, mindfulness, and self-compassion traits). The results showed that the MBSR group exhibited increased emotion differentiation for negative emotions and improvements in various mental health measurements (wellbeing and mindfulness traits) compared to the READ group. However, there were no significant differences in HRV between the two groups, and gains in emotion differentiation did not correlate significantly with changes in mental health outcomes. The findings suggest that MBIs can enhance emotion differentiation as a top-down mechanism and improve mental health outcomes. However, further research is needed to understand the precise psychophysiological mechanisms underlying these effects.